2016
DOI: 10.1289/ehp.1408973
|View full text |Cite
|
Sign up to set email alerts
|

Long-term PM2.5Exposure and Neurological HospitalAdmissions in the Northeastern United States

Abstract: BackgroundLong-term exposure to fine particles (particulate matter ≤ 2.5 μm; PM2.5) has been consistently linked to heart and lung disease. Recently, there has been increased interest in examining the effects of air pollution on the nervous system, with evidence showing potentially harmful effects on neurodegeneration.ObjectiveOur objective was to assess the potential impact of long-term PM2.5 exposure on event time, defined as time to first admission for dementia, Alzheimer’s (AD), or Parkinson’s (PD) disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
212
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(224 citation statements)
references
References 68 publications
8
212
4
Order By: Relevance
“…An increased rate of decline in cognitive function may also be associated with higher air pollution exposures [136]. Some studies have reported associations between exposure to air pollutants and dementia [137, 138], but not all study results support such a relationship [139]. …”
Section: Emerging Adverse Effects Of Outdoor Air Pollutionmentioning
confidence: 99%
“…An increased rate of decline in cognitive function may also be associated with higher air pollution exposures [136]. Some studies have reported associations between exposure to air pollutants and dementia [137, 138], but not all study results support such a relationship [139]. …”
Section: Emerging Adverse Effects Of Outdoor Air Pollutionmentioning
confidence: 99%
“…Among other ambient pollutants, fine particulate matter (PM 2.5 ) has been subjected to extensive investigations Yu et al, 2013). Both short-term and long-term health effects of PM 2.5 were observed in past studies (Yu et al, 2015;Kioumourtzoglou et al, 2016). Epidemiological and toxicological studies have demonstrated that exposure to PM 2.5 is strongly associated with cardiovascular and respiratory diseases (Weichenthal et al, 2016;Yang et al, 2016;Zhang et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter with aerodynamic diameters less than or equal to 2.5 mm (PM 2.5 ) is a serious concern, because it can lead to significant deterioration of visibility and adverse health risks (Meng et al, 2013;Yang et al, 2013;Pui et al, 2014;Kioumourtzoglou et al, 2015). The regional combined pollution characterized by PM 2.5 in Asia is of increasing concern, particularly in China (Hu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%